Advances in radiated power control at DIII-D. (January 2019) - Eldon, D.; Kolemen, E.; Humphreys, D.A.; Hyatt, A.W.; Järvinen, A.E.; Leonard, A.W.; McLean, A.G.; Moser, A.L.; Petrie, T.W.; Walker, M.L.
Highlights: Feedback control of divertor radiated power from has been achieved with N2 seeding. Control works up to 80% radiated power fraction, with steadier control at 55%. DIII-D now has a reliable realtime sensor for radiated power from the lower divertor. Sensor works during changes in strike point position and radiation source location. Abstract: Feedback control of radiated power from the lower divertor P rad, div, L has been implemented in the DIII-D Plasma Control System (PCS). A realtime sensor for P rad, div, L has been constructed from 12 foil bolometer channels which agrees with standard post-shot analysis to within 20%. Results with the 12-channel sensor are compared to initial proof-of-concept tests with a single channel as a proxy for P rad, div, L, showing that the upgraded sensor is necessary to overcome limitations of the proxy channel strategy in DIII-D. Using N2 seeding under feedback control, P rad, div, L has been increased by up to 150% above unseeded levels, and a radiated power fraction frad of 80% has been demonstrated, although feedback controlled gas flow is steadier at frad = 55%. Spatial coverage is broad enough to enable Prad control during the strike point sweeps which are commonly used to generate pseudo-2D divertor Thomson measurements in DIII-D divertor experiments. Use of this control reveals challenges that may affect next step devices, which will require actively controlled extrinsic impurity seeding in order to manage heat loads. When operating at high frad, changes in pedestal Te (caused by ELMs in these experiments but could come from other disturbances) resulted in large perturbations to Prad which were destabilizing to the feedback controller.